Visualising invisibility: photography and physical anthropology in Norway1. Issue 4 (3rd September 2018) - Nielssen, Hilde Wallem
ABSTRACT: This article explores how photographs of Sámi peoples were used in the context of Norwegian physical anthropology in the interwar period, but also how they are re-appropriated in the Lule Sámi community in Tysfjord today. It also demonstrates how photography as used in in the Norwegian racial research publications, although designed to highlight physical characteristics, also include references to cultural characteristics and context. Such inclusion of cultural markers and contextual information may be understood as a strategy to overcome the failure of the scientific community to isolate race as a biological fact. The photographs worked to secure "evidence" where evidence could not be found. This strategy is based on the abundancy, or excess of meaning, of the photographic image as such. The article argues that it is precisely this photographic excess that is the key to understanding why and how photography contributed to establish credibility to a scientific discipline in continuous struggle and with frequent breakdowns. The abundancy, or photographic excess, is also a key to understand how photographs that once were used as instruments of racial research, over time have undergone a series of transmutations of functions and meanings. Thus, racial photographs may acquire new meanings when circulating in time and space.